Analysis of a viscous soft dielectric elastomer generator operating in an electrical circuit. Issue 1 (December 2014) - Bortot, Eliana; Denzer, Ralf; Menzel, Andreas; Gei, Massimiliano
Abstract Dielectric Elastomer Generators (DEGs) are able to convert mechanical work into electric energy. A soft dielectric elastomer generator can be modelled as a strain‐dependent variable capacitor undergoing large viscoelastic deformation. In this work we analyze an electrical circuit for energy harvesting in which the DEG is stretched periodically by a source of mechanical work. Since these devices undergo a high number of electro‐mechanical loading cycles at large deformation, it turns out that viscous effects must be carefully taken into account as they strongly affect the generator performance. (© 2014 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)